Human biomonitoring of toxic and essential metals in younger elderly, octogenarians, nonagenarians and centenarians: Analysis of the Healthy Ageing and Biomarkers Cohort Study (HABCS) in China. (November 2021) - Lv, Yuebin; Wei, Yuan; Zhou, Jinhui; Xue, Kai; Guo, Yanbo; Liu, Yang; Ju, Aipeng; Wu, Bing; Zhao, Feng; Chen, Chen; Xiong, Jiahui; Li, Chengcheng; et al.
Highlights: Gender difference in toxic metals and essential metals partly explain the difference in longevity. Toxic metals such as lead and cadmium were significantly higher in centenarians. Essential metals were sufficient in centenarians and likely to be used as an index of malnutrition. Providing reference values of metals for octogenarians, nonagenarians, centenarians. The top four important metals in longevity were selenium, arsenic, lead and manganese. Abstract: Background: Metals can be either toxic or essential to health, as they play different role in oxidative stress and metabolic homeostasis during the ageing process. Population-based biomonitoring have documented levels and ranges in concentrations among general population of 0–79 years of age. In people aged 80 and above, toxic metals and essential metals may have different risk profiles, and thus need to be better studied. Objective: Our aim is to investigate concentrations of toxic metals (arsenic, cadmium, lead and mercury) and essential metals (chromium, cobalt, molybdenum, manganese, nickel and selenium) and their role in diseases, nutritional status among younger elderly, octogenarians, nonagenarians and centenarians. Methods: A total of 932 younger elderly, 643 octogenarians, 540 nonagenarians, 386 centenarians were included from the cross-sectional Healthy Aging and Biomarkers Cohort Study in 2017–2018. Blood or urine biological substrates were collected from each participant to determine the concentrations of toxic metals and essential metals by inductively coupled plasma mass spectrometry. Random forest was constructed to rank the importance of toxic metals and essential metals in longevity. LASSO penalized regressions were performed to select the most significant metals associated with diseases and nutritional status, of which simultaneously included all metals and adjusted for the confounding factors. Results: Compared to women, we found higher biomarker concentrations in men for toxic metals (41.2 µg/L vs 34.4 µg/L for blood lead, 1.56 µg/L vs 1.19 µg/L for blood mercury) and lower concentration of essential metals (0.48 µg/L vs 0.58 µg/L for blood molybdenum, 10.0 µg/L vs 11.1 µg/L for blood manganese). These factors may contribute to gender difference observed in longevity, that women live longer than men. Blood lead and urine cadmium tended to increase with age ( P  <0.001); blood cobalt, molybdenum, manganese increased with age, blood selenium decreased with age while the prevalence of selenium deficiency was extremely low in centenarians. Among toxic metals and essential metals, LASSO penalized regression identified the most significant metals associated with chronic kidney disease was cadmium and arsenic; and it was manganese, cobalt, and selenium for diabetes; it was selenium, molybdenum, lead for anemia; it was mercury for underweight. In random forest model, the top four important metals in longevity were selenium, arsenic, lead and manganese both in men and women. Conclusions: Generally, toxic metals levels were significantly higher while essential metals were relatively sufficient in Chinese centenarians. Toxic metals and essential metals played different role in diseases, nutritional status and longevity in the process of aging. Our research provided real world evidence of biomonitoring reference values to be used for the ongoing population health surveillance in longevity.